EP806 First insight of a tailoring chemotherapy intensity regimen in a real life cohort of elderly patients with ovarian cancer: the CIRCE study. (1st November 2019) - Bortot, L; Bartoletti, M; Basile, D; Gerratana, L; Corvaja, C; Lisanti, C; Pelizzari, G; Garattini, SK; Garutti, M; Buriolla, S; Da Ros, L; Bolzonello, S; et al.
Abstract : Introduction/Background: Women aged ≥65 represent nearly 50% of ovarian cancer (OC) patients (pts). However, elderly OC pts are less likely to receive optimal treatment. Furthermore, they are significantly under-represented in clinical trials and multidimensional geriatric assessment is still underused. The present study aims to provide an overview of real-life treatment strategies for elderly advanced-OC pts and to investigate clinico-pathological features that could potentially drive choice of first-line treatment. Methodology: A retrospective analysis was conducted on a consecutive series of 45 OC pts aged ≥69 treated with first-line chemotherapy (1L_CT) from 2011 to 2018 at CRO Aviano National Cancer Institute (Italy). Factors associated with treatment choice and rate of adverse events were investigated through Fisher-exact test; differences in progression free survival (PFS) and overall survival (OS) were tested by log-rank test. Results: 67% of pts received 1L_CT with a standard carboplatin-paclitaxel combination (CPC). Conversely, 33% received a monotherapy (MT) (31% with carboplatin, 2% with paclitaxel). ECOG PS ≥1 was the only factor significantly associated with choice of MT (P=0.021). No differences were observed between CPC and CPC with dose reductions (CPCdr), neither in terms of PFS (HR=1.29 P=0.59) nor OS (HR=1.40 P=0.56). On the other hand, MT was associated with shorter PFS (HR=4.35 P=0.001) and OS (HR=4.48 P=0.005). No differences in treatment discontinuation rate, neutropenia, thrombocytopenia, neuropathy, constipation, diarrhoea and asthenia in CPC, CPCdr and MT were detected (P>0.05). Conclusion: The present study confirms CPC as the standard first-line chemotherapy also in advanced OC elderly pts and suggests that CPCdr is preferable to MT regimens. Notwithstanding the limitations due to the small sample size, the evaluated regimens showed a comparable toxicity profile. Notably, clinical decision-making was mainly driven by PS ECOG highlighting the pivotal role of multidimensional geriatric assessment for pts stratification. Further prospective studies are needed to investigate improved tailored strategies. Disclosure: Nothing to disclose.